Diagnostika aktivních částic generovaných plazmatem mikrovlnného výboje v interakci s kapalinami - Kovaříková, Kateřina (Vysoké učení technické v Brně. Fakulta chemická, 2020)
Tato bakalářská práce se v první části zabývá problematikou elektrických výbojů generovaných v plynech a nad hladinou kapalin. Zaměřuje se na tvorbu aktivních částic v plazmatu a jejich následné analyzování vhodnými analytickými metodami. Druhá část se zabývá identifikací aktivních částic v plazmatu mikrovlnného výboje v plynu a při interakci s povrchem vodného roztoku. Cílem práce bylo prostudování vlivu experimentálních podmínek na tvorbu aktivních částic, konkrétně dusičnanových a dusitanových iontů.

The first part of this Bachelor’s thesis describes problems of electric discharges in gas and on a surface of water solutions. It focuses on the generation of the active particles that are generated during the discharge and their subsequent analysis by appropriate analytical methods. The second part focuses on identification of the active particles that are generated during the microwave discharge in gas phase and during the interaction with water solution surface. The aim is to determine the influence of experimental conditions on the information of the active particles, specifically the nitrates and nitrite ions.
Diagnostics of active particles generated by the interaction of plasma microwave discharge with liquids
Keywords: Mikrovlnný výboj; diagnostika plazmatu; plazma v kapalinách; dusičnany; dusitany; microwave discharge; plasma diagnostics; plasma in liquids; nitrates; nitrites